Solution-Focused Brief Group Counseling as an Effort to Reduce Phubbing Behavior Among High School Students - Pratiwi, Awalya Siska; Setiyowati, Arbin Janu; Hambali, IM; Zulkuple, Siti Syazwani (Jurnal Kajian Bimbingan dan Konseling, 2025)
The act of phubbing has been observed to disengage from their surroundings, often finding greater comfort in solitude with their mobile phones. The research objective was to ascertain the efficacy of solution-focused brief group counseling to reduce phubbing behavior in high school students. This study employed a quasi-experimental quantitative research methodology with a pretest-posttest control group design. A total of 10 students, exhibiting a high level of phubbing behavior, were divided into two groups: the experimental group and the control group. The results of the Two-Independent-Sample Test-Mann-Whitney U test are presented in the Asymp .sig column, with a value of 0.036 (0.036 <0.05). The results show that the value of Asymp. sig. which is smaller than 0.05, that is, there is a significant difference between the experimental and control groups. These results indicate that solution-focused brief group counseling may be an effective approach to reducing phubbing behavior in high school students.